MyD88 or TRAM knockdown regulates interleukin (IL)-6, IL-8, and CXCL12 mRNA expression in human gingival and periodontal ligament fibroblasts - Morandini, Ana Carolina; Souza, Pedro Paulo Chaves [UNESP]; Ramos Jr., Erivan Schnaider; Costa, Carlos Alberto Souza [UNESP]; Santos, Carlos Ferreira (Wiley, 2013)
Background: In a previous report, it was shown that Toll-like receptor (TLR) 2 knockdown modulates interleukin (IL)-6 and IL-8 but not the chemokine CXCL12, an important mediator with inflammatory and proangiogenic effects, in human gingival fibroblasts (HGF) and human periodontal ligament fibroblasts (HPDLF). This study investigates whether knocking down two important TLR adaptor molecules, such as myeloid differentiation protein 88 (MyD88) and TRIF-related adaptor molecule (TRAM), could affect mRNA expression of IL-6, IL-8, and CXCL12 in HGF and HPDLF. Methods: After small interfering (si) RNA-mediated silencing of MyD88 or TRAM, HGF and HPDLF were stimulated with Porphyromonas gingivalis (Pg) lipopolysaccharide (LPS) or two synthetic ligands of TLR2 (Pam2CSK4 and Pam3CSK4) for 6 hours. IL-6, IL-8, and CXCL12 mRNAs were evaluated by quantitative polymerase chain reaction. Results: Knockdown of MyD88 or TRAM partially impaired the IL-8 mRNA upregulation in both fibroblast subpopulations. Similarly, IL-6 upregulation was partially prevented by siMyD88 or siTRAM in HGF stimulated with Pg LPS, as well as in both fibroblast subtypes challenged with Pam2CSK4. Conversely, constitutive CXCL12 mRNA levels were upregulated by MyD88 or TRAM knockdown in non-stimulated cells. Conclusions: These results suggest that TLR adaptor molecules knockdown, such as MyD88 or TRAM, can decrease IL-6 and IL-8 mRNA and increase CXCL12 mRNA expression in HGF and HPDLF. This can be an important step for better understanding the mechanisms that control the inflammatory cytokine and chemokine expression, which in turn contributes to periodontal pathogenesis.
Keywords: Cytokines; Fibroblasts; Lipopolysaccharides; Myeloid differentiation factor 88; Porphyromonas gingivalis